2016
DOI: 10.3390/s16111893
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PZT Coating Thickness and Electrical Pole Alignment on Microresonator Properties

Abstract: With increasing technical requirements in the design of microresonators, the development of new techniques for lightweight, simple, and inexpensive components becomes relevant. Lead zirconate titanate (PZT) is a powerful tool in the formation of these components, allowing a self-actuation or self-sensing capability. Different fabrication methods lead to the variation of the properties of the device itself. This research paper covers the fabrication of a novel PZT film and the investigations of its chemical, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Moreover, the thickness effect would become more pronounced when the films’ thickness vary from micrometer to nanometer scale [15]. Previous investigations mainly focus on the study of PZT films’ thickness effect on microstructure and ferroelectric properties [16,17,18,19]. Ong et al found that tensile stresses decrease and the dielectric constant increases with the increasing thickness of the PZT film, ranging from ~100 to ~500 nm [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thickness effect would become more pronounced when the films’ thickness vary from micrometer to nanometer scale [15]. Previous investigations mainly focus on the study of PZT films’ thickness effect on microstructure and ferroelectric properties [16,17,18,19]. Ong et al found that tensile stresses decrease and the dielectric constant increases with the increasing thickness of the PZT film, ranging from ~100 to ~500 nm [16].…”
Section: Introductionmentioning
confidence: 99%
“…These microcantilevers were also tested experimentally. Geometric parameters of the OPT RAT model ( l = 1 mm, width 0.1 mm) were used to fabricate a prototype of the piezoelectric VEH by employing the proposed rationally-shaped substrate made of nickel that was covered with three segments of a screen-printed piezocomposite layer (Polyvinyl butyral 20% mixed with PZT nanopowder) with electrodes [ 20 ].…”
Section: Study Of Piezoelectric Vibro-impacting Veh Prototype Basementioning
confidence: 99%
“…Therefore, traditional acoustophoresis devices must be improved. Development of lead-free piezoceramics by replacing traditional lead zirconium titanate (PZT) ceramics [ 12 , 13 , 14 ] has gained huge interest in the field of biologically compatible manipulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…PZT for over 50 years has been a very popular and widely studied ceramic allowing to synthesize a large number of materials with different properties due to the range of Zr:Ti ratios used in synthesis process [ 12 , 13 , 14 , 15 ]. However, in the past few years the toxicity of lead oxide was highly discussed encouraging the development of lead-free piezoceramics and devices for medical, pharmaceutical, and other applications.…”
Section: Introductionmentioning
confidence: 99%